Political assassination in international and domestic law: the use of poisonous weapons - Galkoviča, Poļina (Riga Graduate School of Law, 2021)
The notion of political assassination, as well as of the use of poisonous weapons, is not a new phenomenon. This practice was always known to the world of intelligence, as well as states often decided to resort to state-sponsored killings. For the purposes of this Bachelor Thesis, emphasis is put on the Russian practice of political assassination with the use of poisonous weapons, and the prominent cases of assassinations of Alexander Litvinenko, Sergei Skripal and Alexei Navalny will be described in this work, as well as further analysed from the perspective of the established international legal norms and the applicable Russian domestic law. Sometimes states choose to assassinate in such a way that it is hard to detect, whether they are behind the attack or not, but on other occasions their intent is to send a powerful message, while formally denying the involvement in any way related to the acts of assassination. The Russian extensive practice of political assassination refers to its hybrid warfare strategy, and the use of toxic substances is still seen as a signature weapon for the Kremlin.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Hybrid warfare; Chemical weapons; Russian Federation